International Early Learning and Child Well-Being Study: uma análise crítica sobre avaliações em larga escala para a educação infantil - Galbiatti, Luísa Fagá (Universidade Federal de São Carlos, 2025)
This study presents and analyzes the 2020 report of the International Early Learning and Child Well-Being Study (IELS), a test funded by the OECD to assess the early learning of children aged 5 to 6 in terms of cognitive and emotional skills. Through document analysis and a literature review, the impact of Large-Scale Assessments (LSAs) on Early Childhood Education is discussed and understood. Based on the study of neoliberal policies, which transform education into a commodity, the research concludes that this type of assessment prioritizes quantitative results over a holistic and contextualized education. Finally, the study proposes a reflection on alternatives to LSAs, inspired by more democratic and humanistic approaches, such as Paulo Freire's pedagogy, aiming for an education that values equity, diversity, and the comprehensive development of students.
International Early Learning and Child Well-Being Study: a critical analysis of large-scale assessments for early childhood education
Keywords: IELS; Avaliações em larga escala; Neoliberalismo; Políticas públicas; Educação; IELS; Large-Scale Assessments; Neoliberalism; Public policies; Education; CIENCIAS HUMANAS::EDUCACAO